Effects of Myrtus communis extract treatment in bile duct ligated rats - ŞEN, ALİ; ERCAN, FERİHA; ŞENER, GÖKSEL; BİTİŞ, LEYLA (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2016)
Background: The aim of our study was to investigate the antifibrotic and antioxidant effects of Myrtus communis subsp. communis (MC) extract against liver injury and fibrosis occurring in rats with biliary obstruction. Materials and methods: The rats were randomized into four groups (n = 8). Control group (C), MC-administrated group (MC), the bile duct ligation (BDL), and BDL + MC groups. MC was administered at a dose of 50 mg/kg a day orally for 28 days. In blood samples, total bilirubin, direct bilirubin, alanine aminotransferase, aspartate aminotransferase levels, tumor necrosis factor-alpha, and interleukin-1 beta measurement were measured. Oxidative injury was examined by measuring luminol and lucigenin chemiluminescence, malondialdehyde and glutathione levels, superoxide dismutase and myeloperoxidase activities. Transforming growth factor-beta and hydroxyproline levels were measured for analyzing fibrosis. The hepatic injury was also analyzed microscopically. Results: Plasma total bilirubin, direct bilirubin, alanine aminotransferase, aspartate aminotransferase, tumor necrosis factor-alpha, and interleukin-1 beta levels were found significantly high in the BDL group, while these values significantly decreased in the BDL group treated with MC. On the other hand, the glutathione and superoxide dismutase values significantly decreased in the BDL group compared to the control group but increased markedly in BDL + MC group compared to the BDL group. Malondialdehyde levels, myeloperoxidase activity, tissue luminol, lucigenin, transforming growth factor-beta, and hydroxyproline levels when compared with the control group increased dramatically in the BDL group and reduced the MC + BDL group. Conclusions: Our results suggest that MC protects the liver tissues against oxidative damage following BDL via its radical scavenging and antioxidant activities, which appear to involve the inhibition of tissue neutrophil infiltration. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Myrtus communis subsp communis; Bile ductal ligation; Hepatic fibrosis; Oxidative injury; BILIARY OBSTRUCTION; OXIDATIVE STRESS; LIVER FIBROSIS; MOUSE MODEL; ANTIOXIDANT ACTIVITIES; REACTIVE OXYGEN; HEPATIC-INJURY; ESSENTIAL OILS; TNF-ALPHA; L.